Relevancies of Buddhism on International Relations: Analysis of eightfold paths of Buddhism (Research Nepal Journal of Development Studies, 2022)
Buddha's thoughts are not only recognized as philosophy or religion but also applied significantly as credence in economic, political, and international relations. Buddha’s thoughts have been acknowledged as a more gorgeous and vital tool to upkeep better relations practically. Through a highly rationalized and applied interpretation of the thoughts, it has been pragmatized in real events as peace-keeping instruments among geopolitical cults. Foreign policy among states has become chaotic and inconsistent in recent years. The five principles of peaceful coexistence of foreign policy and the eight-fold new path of Buddhism have numerous potential implications for driving the globe toward rectifying a pragmatic approach to international relations.